Estudo da secagem de jabuticaba (polpa e casca) pelo método de camada de espuma - Ferreira, Mário Nogueira (2017)
The objective of this work was to characterize the pulp + jabuticaba shell, the foams of the formulations (F1, F2, F3, F4) and the pulp + jabuticaba shell powder by the foam layer method. It was used jabuticaba of the variety M. cauliflora sp (jabuticaba sabará), harvest 2016. The pulp + jabuticaba bark were characterized as centesimal composition, hydrogenation potential, total titratable acidity, total soluble solids, energy value, water activity and color (a*, b *, L *, h * and C *). The foam was characterized regarding density, the percentage of expansion, stability, and fraction of drained volume, drying curves and mathematical modeling. The pulp + bark of jabuticaba powder was also characterized for the adsorption isotherm, scanning electron microscopy (SEM), antioxidant potential by the DPPH method, ABTS and FRAP, total phenolics, condensed and hydrolyzed tannins, absorption indexes and solubility in water (AI/SW) and milk (IAL / ISL) and oil absorption index (OAI). It was observed that the moisture content, SST, pH, acidity, water activity and color did not change, while all other analyzes were influenced. Formulation F3 was the one that best fit the foam evaluation criteria. The model of Wang and Singh presented the lowest reduced chi-square (χ²) and the highest coefficients of determination (R²), whereas the Page model obtained higher values for the drying rate and lower values for the internal resistance to the formulation F3. It was verified that the formulation F3 presented greater reduction of the moisture ratio as a function of time compared to the other formulations during processing. Therefore, a model can be adjusted in certain bands and not in others, which limits the application of empirical models. The results obtained in this study demonstrate that the pulp foam drying + jabuticaba bark can make a promising alternative in the post harvest of this important fruit since it allows the retention of nutritional components of interest in this product and thus increases the consumption Of this product in powder form.